Analysis of Price, Location, and Service Quality on Customer Satisfaction at Kenzie Barbershop in Medan City - Baihaqqi Aqil; Ocdy Amelia (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The purpose of this article is to examine how customer happiness at Kenzie Barbershop in Medan is impacted by pricing, location, and service quality. 96 respondents (customers) made up the sample for the quantitative approval. The findings indicate that customer happiness is significantly positively impacted by service quality, with location and pricing coming in second and third. The results indicate that in order to boost client happiness, Kenzie Barbershop should give priority to enhancing service quality. In order to draw in and keep clients, the barbershop should also think about its advantageous location and affordable prices.At Kenzie Barbershop, pricing, location, and service quality all have a positive and considerable simultaneous impact on client satisfaction.